Thymoquinone protects against cardiac damage from doxorubicin-induced heart failure in Sprague-Dawley rats. Issue 26 (18th April 2018) - Pei, Zuowei; Hu, Jiahui; Bai, Qianru; Liu, Baiting; Cheng, Dong; Liu, Hainiang; Na, Rongmei; Yu, Qin
Abstract : Heart failure is a complex end stage result of various cardiovascular diseases, and has a poor prognosis. Abstract : Heart failure is a complex end stage result of various cardiovascular diseases, and has a poor prognosis. The mechanisms for the development and progression of heart failure have always been an important topic in cardiovascular research, and previous studies have shown that thymoquinone (TQ) protects against cardiotoxicity and cardiac damage. The aim of this study was to investigate the possible protective effects of thymoquinone against cardiac damage in doxorubicin (DOX)-induced heart failure in Sprague-Dawley Rats (SDR). Forty-five male SDR were randomly divided into three groups and administered different treatment regimens for 8 weeks. Left ventricular fractional shortening (LVFS) and ejection fraction (LVEF) were higher in the DOX + TQ group than those in the DOX group. Significant pathophysiology changes (HE and Masson staining) were observed in rats of the DOX group compared to those of the DOX + TQ group. The addition of Thymoquinone inhibited DOX-induced cardiac fibrosis (TGF-β, Smad3, collagen I, collagen III, and α-SMA) and apoptosis (P53, bcl-2, caspase-3, caspase-9, and BAX) in SDR, indicating that thymoquinone may be a potential therapeutic target for cardiac damage caused by DOX-induced heart failure.